Epidemic Louse-Borne Typhus, and biological and socio-economic factors: a review of disease events during the Irish potato famine and recent history - Lona, Antoinette (Kansas State University, 2021)
Epidemic Louse-Borne Typhus (EL-BT) poses an epidemiological threat to global public health. Rickettsia prowazekii (R. prowazekii) is the etiologic agent of EL-BT. This thesis inductively identifies causative factors of EL-BT events, and does so using an array of historical outbreaks over the last century and a half. Four cases were historically reviewed: the 19th-century Irish potato famine and EL-BT epidemic, and three 20th-century EL-BT events. The thesis uses these past and contemporary real-life accounts of R. prowazekii events, and explains how both biological and socio-economic factors uniquely birth and perpetuate EL-BT outbreaks. Both historically and contemporarily, the results show an empirical relationship between socio-economic and biological factors and EL-BT disease events. The causality of EL-BT may be attributed to poverty (a socio-economic factor), homelessness (a socio-economic factor), unsanitary conditions (both a socio-economic and biological factor), famine (a biological factor), and body lice infestation (a biological factor). Public health practitioners and policymakers are right to focus programs and policies on not only biological, but also expressly socio-economic, factors in order to address EL-BT. U.S. policymaking efforts, including recent administration budget requests, signal an opportunity to intentionally address both biological and socioeconomic causes of not only EL-BT, but also other disease events.
Keywords: Irish Potato Famine; Typhus; Louse-Borne Typhus; Socio-economic factors